Housing as urbanism: a policy to discourage urban sprawl and provide well-located and affordable housing in South Africa - Van Niekerk, Brendon (University of the Free State, 2018)
The concept of ‘housing as urbanism’ considers the social, political and economic components of housing, which, in reality, translates to housing that is closer to employment, municipal services, public spaces, healthcare, schooling facilities and social services, while also providing the household with the physical infrastructure necessary for a good quality of life. These considerations have not been included in the mass roll-out of low-income housing programmes by the South African government to date. A series of case studies show that, in South Africa, a more compact urban form does not necessarily lead to one that is less expensive than a sprawled urban form, due to infrastructure thresholds, capacities, location, land-use mix, and density variations over time and space. Due to the complex interrelations between land values in space, the costs of buildings and urban services, the relative cost of transport and the excess capacities in infrastructure systems, a simple dichotomous ‘sprawled’ versus ‘compact’ approach to housing location and urban development is not appropriate. Investigations of individual sites need to be performed, in order to understand the social, political and economic benefits, which will accrue to the households from their location in the city. The case studies also indicate that, over the long term, the overall cost of housing developments that are better located, subscribing broadly to the principles of ‘housing as urbanism’, is likely to be less expensive to municipalities and the development’s residents than poorly located, sprawled housing developments. Decisions taken which consider the principles of ‘housing as urbanism’ can help create a more efficient urban form, freeing up resources for both urban residents and public-sector organisations.
Keywords: Affordable housing; Housing as urbanism; Fiscal impact study; Urban efficiency; Urban sprawl